Wheat bran valorization for proteins and bioactive peptides - Stump, Michael (My University, 2025)
Over the past several decades, significant efforts have been made towards the valorization and value-addition of agricultural waste and byproducts. One area being explored is the valorization of wheat bran: a major byproduct of the wheat milling industry. Wheat bran has excellent nutritional value, containing approximately 10 to 15% protein by weight. However, its direct incorporation in human diets has been limited due to unappealing sensory characteristics, which has resulted in wheat bran being used primarily for animal feeds. To address this challenge, we propose that the separation of proteins in wheat bran from undesirable components could enhance its suitability as a food ingredient for human consumption. In addition to the use of wheat bran protein as a food ingredient, there has also been a surge in the study of bioactive peptides for use in nutraceuticals, or ‘functional foods”. We have also proposed that wheat bran proteins could be used as a readily available feedstock for the production of bioactive peptides. The objectives of this study were specifically focused on the following goals: 1) Optimization of protein extraction efficiency and purification methods, 2) Production and characterization of peptides from purified wheat bran proteins, and 3) Screening of wheat bran proteins and peptides for antioxidant and anti-aging activities using in-vitro bioactivity assays. The experiments conducted in this study focused on optimization of protein extraction methods based on Osborne fractionation, alkaline extraction, and deep-eutectic solvent (DES) extraction methods. Each of these protocols were performed and evaluated via LECO analysis of the bran residues after extraction and by performing Bradford assays on protein extracts. A chromatographic purification method was then adapted for use with wheat bran protein extracts using inexpensive, 500Å underivatized silica gel with a two-phase capture and elution phase step gradient. The effectiveness of this method was further confirmed using size exclusion high performance liquid chromatography (SEC-HPLC) analysis. The purified proteins were then used to produce peptides via enzymatic hydrolysis catalyzed by pepsin and trypsin. Each Osborne protein fraction, and each corresponding tryptic- and peptic-peptide were then screened for potential biological activity via the DPPH assay, as well as the percent inhibition of enzymes associated with skin cellular aging. The results of these assays were evaluated using one-way ANOVA statistical analysis, and the activity of each protein or peptide sample was compared to the standard, ascorbic acid. The results of this study showed that the modified Osborne fractionation extraction protocol was the most efficient, achieving a percent recovery of 74.75% of the total protein in the bran. The alkaline extraction and the DES extraction achieved percent recoveries of only 24.77% and 24.84% of the total protein in the bran, respectively. The purity of each Osborne fraction extracted from wheat bran was then tested using SDS-PAGE and SEC-HPLC. Significant impurities were observed in every sample as visible in the SEC-HPLC chromatograms. These impurity peaks disappeared from the chromatograms of proteins purified by the 500Å silica gel column and matched the retention times of the species isolated during the capture phase. This confirmed that the adapted 500Å silica gel column method successfully and reliably removed lower molecular weight impurities from each protein fraction. Analysis of the bioactivity assay results using the one-way ANOVA identified seven different peptide and protein samples that were statistically comparable to ascorbic acid. UPLC-MS analysis of these samples confirmed the presence of peptides through observation of characteristic peptide clusters in the mass spectra. This study details the optimization of a protein extraction method, the adaptation of an inexpensive, efficient, and effective method for purifying wheat bran proteins, and the screening of wheat bran proteins and protein hydrolysates for in-vitro biological activity. The results of these studies suggest that wheat bran has excellent potential for valorization from a low-value industrial byproduct into more valuable nutraceutical products for the consumer market.
Keywords: Valorization; Wheat bran; Anti-aging; Bioactive peptides; Nutraceuticals; Proteins